ダイ 31 ジ ナンキョク チイキ カンソク タイ アスカ カンソク キョテン エットウ 1990 ホウコク - 白石, 和行; シライシ, カズユキ; Shiraishi, Kazuyuki (1992)
P(論文) 8人の隊員からなる第31次南極地域観測隊あすか越冬隊は1989年12月25日から1990年12月26日までの367日間, あすか観測拠点を運営し観測を行った。越冬期間中の主要な目的は, 気象観測と宙空系のオーロラを主とした観測である。雪氷系の研究観測や設営工学的観測も副次的に実施した。このほかに, セールロンダーネ山地において, 補足的な地質調査と寒冷医学実験を行うために調査旅行が積極的に行われた。また, 越冬に先だって, 第31次夏オペレーション期間中は, ヘリコプターオペレーションの根拠地として「あすか」が使われたため, その後方支援を行うことも大きな任務であった。これらの諸観測・調査はほぼ順調に経過し所期の目的を果たした。 The wintering party at Asuka Station (71°31′34″S, 24°08′17″E, 930m a. s. l.) by the 31st Japanese Antarctic Research Expedition (JARE-31), consisting of 8 personnel, maintained Asuka Station continuously from December 25,1989 to December 26,1990. The main scientific programs of the party were the meteorological observation and studies of upper atmosphere physics. Other programs comprised geological investigation and search for meteorites in the Sor Rondane Mountains, and medical-biological studies, glaciological studies and logistic survey of the housing at Asuka Station and its vicinity. During the 1989/1990 summer season, Asuka Station was used as the base camp for the helicopter operation in the Sor Rondane Mountains. All programs were carried out successfully during the wintering and the Station was succeeded by JARE-32. departmental bulletin paper